Respon Hukum Nasional terhadap Perubahan Sosial Di Masa Pandemi Covid-19 di Indonesia - Nabiila, Fathiya; Irawan, Farid Pardamean Putra (Morality: Jurnal Ilmu Hukum, 2022)
Law and the phenomenon of social change are two interrelated elements, where legal change is a result of social changes that occur in society. Covid-19 causes legal changes in response to changes that occur in society. The purpose of this writing is to increase knowledge related to the correlation of national law with social phenomena that occur. This study uses a juridical normative method, by analyzing the relationship between legal rules and social change, and examines the response of national law during a pandemic. Social change is influenced by several factors including population, physical habitat, technological developments, community structure, and culture. The law is said to have been successful in its implementation when it can move the community according to what is desired, in the sense that individuals can obey what has been determined by law. Some time ago, the world was shocked by the emergence of the Covid-19 virus, which is easy to spread and can lead to death. The government is required to ensure the safety and protection of citizens from this dangerous virus. In its progressive steps, the government has made a series of rules to minimize the impact of losses, both from the fatalities identified by the Covid-19 virus, or losses from the economic aspect caused by the Covid-19 outbreak.